PENGARUH SINAR GAMMA PADA BENIH MANGGIS (Gardnia mangostana L.) [Effects of Gamma Rays on Mangosteen (Garcinia mangostana L.) Seeds] - Hutabarat, Dameria (BERITA BIOLOGI, 2000)
Mangosteen seeds were irradiated with gamma rays from Co dosages 2.5 Gy, 5 Gy, 7.5 Gy, 10 Gy, 20 Gy, 40 Gy and 60 Gy. The germination rates of irradiated seeds were reduced by an average of 20 % at 20 Gy, 67 % at 40 Gy and no seed germination at 60 Gy.The effects of the treatment on the survival of irradiated seeds were observed.Gamma rays at low dosage (2.5 Gy) was stimulating to seedling growth. The best dosages for inducing variation were around 10 - 20 Gy;variation induced by the treatment included total leaves number and seedling height.